Metaphorical Salience in Artistic Text Processing: Evidence From Eye Movement. (August 2015) - Novikova, Eleonora G.; Janyan, Armina; Tsaregorodtseva, Oksana V.
The study aimed to explore processing difference between a literal phrase and a metaphoric one. Unlike artificially created stimuli in most experimental research, an artistic text with an ambiguous binary metaphoric phrase was used. Eye tracking methodology was applied. Results suggested difference between the two types of phrases in both early and late processing measures.